Redesign Interior Brand Puratos, Distributor Bakery di Bali - Antonio Gerard Prananta; Sriti Mayang Sari (Intra, 2018)
People in Indonesia this year have started to care about what they consume. This will affect food brands to create new innovations continuously in order to complement the consumer’s needs and desires. It started a competition between several brands in order to get most customers. In addition, through the innovations made, store and office interior also play an important role in attracting consumer’s interest and desires. This brings up the need of interior brand Puratos redesign. The